2007
DOI: 10.1007/bf03033897
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity implications in brain disease: Neuronal substrates of symptom profiles

Abstract: The neuronal substrates underlying aspects of comorbidity in brain disease states may be described over psychiatric and neurologic conditions that include affective disorders, cognitive disorders, schizophrenia, obsessive-compulsive disorder, substance abuse disorders as well as the neurodegenerative disorders. Regional and circuitry analyses of biogenic amine systems that are implicated in neural and behavioural pathologies are elucidated using neuroimaging, electrophysiological, neurochemical, neuropharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 229 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…Taken together, the results of the psychiatric patient group and healthy control group are reconcilable with several other observations in illustrating the complex associations between affective personality, stress, energy, and dispositional optimism, not least in possibly underlying comorbidity (Palomo et al, 2007).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Taken together, the results of the psychiatric patient group and healthy control group are reconcilable with several other observations in illustrating the complex associations between affective personality, stress, energy, and dispositional optimism, not least in possibly underlying comorbidity (Palomo et al, 2007).…”
Section: Discussionsupporting
confidence: 55%
“…It indicated that to a marked extent only two of the attributes made a contribution; negative affect was directly predictive whereas positive affect was counterpredictive (see Table 3). This important result − that stress could be predicted from negative affect − has been observed quite regularly (Archer, Adolfsson, & Karlsson, 2008;Archer, Adrianson, Plancak, & Karlsson, 2007;Palomo, Beninger, Kostrzewa, & Archer, 2007). Although stress was also counterpredicted from positive affect, optimism -as measured by life orientation -was found not to affect stress.…”
Section: Discussionmentioning
confidence: 65%
“…The present findings implicate further glutamatergic-dopaminergic interactions as expressed by symptom profiles under brain disease states (cf., Palomo et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…It should be noted also that bulimia nervosa is associated with response inhibition deficits and higher impulsiveness (BIS-11) scores (Kemps and Wilsdon, 2010). Comorbid aspects of clinical impulsiveness remain an issue in the pathophysiology of neuropsychiatric disorders (Palomo et al 2007b). Both ADHD and pediatric bipolar disorder (PBD) are characterized by inattention, impulsiveness, lack of behavioural inhibition and deficits in cognitive flexibility and sustained attention (Galanter and Leibenluft, 2008;Pavuluri et al, 2006), the latter generally associated with emotional dysregulation, elated mood, irritability, increased energy and disinhibition (Pavuluri et al, 2007Pavuluri and Passarotti, 2008).…”
Section: Introductionmentioning
confidence: 99%